Digital Portfolio-Based Assessment in EFL Contexts: A Systematic Literature Review - Alvons Habibie; Adimawati Helingo; Titin Suhartini Kaaba; Hasan Ayuba (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2026)
This review summarizes research on digital portfolio-based assessment in EFL to address gaps in knowledge about teaching benefits, technology tools, student involvement, cross-cultural use, and assessment methods. Following PRISMA 2020 guidelines, fifty highly relevant studies published between 2016 and 2025 were systematically identified, screened, and analyzed using thematic and chronological synthesis frameworks. Findings indicate that digital portfolios significantly enhance language skills, self-regulated learning, and reflective practices while supporting formative assessment through multimodal feedback. However, technological barriers, increased workload, and inconsistent instructional design limit their effectiveness. Diverse platforms including Facebook, Google Sites, Edmodo, Moodle, and AI-integrated tools such as Notion AI facilitate accessibility and collaboration but face infrastructural and digital literacy challenges. Cross-cultural variations underscore the need for context-specific training and policy support. The review concludes by calling for standardized assessment frameworks, longitudinal research designs, and targeted teacher professional development to optimize the implementation of digital portfolios in global EFL education.